A Techno-economic evaluation of integrating first and second generation bioethanol production from sugarcane in Sub-Saharan Africa - Van der Westhuizen, Willem Andries (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScEng)-- Stellenbosch University, 2013.